New Astrophysical Mechanism of Disk-Shaped Galaxies’ Rotation by the Theory of Non-Inflationary Cosmology - A. K. Avetissian (ՀՀ ԳԱԱ հրատ.)
The original astrophysical mechanism for the explanation of observed unique phenomenon of disk-shaped galaxies’ rotation character has been revealed within the frame of Non-Inflationary Cosmology, established and developed by author. Հեղինակի կողմից ստեղծված և զարգացված Ոչ-ինֆլյացիոն կոսմոլոգիայի տեսության շրջանակներում բացահայտվել է սկավառակաձև գալակտիկաների պտույտի ինքնատիպ բնույթը տեսականորեն բացատրող նոր աստղաֆիզիկական մեխանիզմ: В рамках созданной и развитой автором теории Неинфляционная космология выявлен новый астрофизический механизм, иллюстрирующий наблюдаемый уникальный характер феномена вращения дискообразных галактик.
Keywords: Astronomy; Astrophysics; Science